Flash sintering behaviour of 8YSZ-NiO composites. Issue 22 (15th November 2022) - Bhandari, Subhadip; Mishra, Tarini Prasad; Bram, Martin; Guillon, Olivier; Yadav, Devinder
Abstract: Flash sintering is an electric field/current assisted sintering technique, which is reported to lower the furnace temperature and to reduce sintering time significantly. In this work, we have studied the processing of 8YSZ/NiO composites by flash sintering, for the first time. Two composites, with different amount of NiO (one below the percolation limit and another one above it) were processed in two different sintering atmospheres. Constant heating rate experiments were performed to know the minimum furnace temperature required to flash sinter the samples for a given applied electric field. Subsequently, isothermal flash sintering experiments were performed at different current densities. The flash onset temperature of the composites was lower in the reducing atmosphere compared to in air. The power dissipated in stage III of the flash was strongly influenced by the composite composition and the sintering atmosphere. The extent of densification in the composites was controlled by the current density. The composites were densified up to a relative density of ∼90% in 30 s when flash sintered in air. In reducing atmosphere, there was in-situ reduction of NiO to Ni. As a result, for composites containing NiO above the percolation limit, the current preferentially flew through the in-situ formed metallic phase and there was no densification in the composite in reducing atmosphere. Phase and microstructure evolution in the composites was studied through XRD, SEM and EDS. With proper control of the electrical parameters (electric field and current density), composites with controlled porosity can be processed through flash sintering which may have applications for solid oxide fuel cells.